El cobro indebido por la prestación de servicios financieros no autorizados por el titular de la cuenta bancaria - Freddy Ricardo, Pilamunga Tomarema (2021)
In this research work, an analysis is carried out of the actions of the institutions of the private sector financial banking system, which do not always observe the norms established in the Organic Monetary and Financial Code and, in some instances, have violated the rights of the financial users, especially when in these institutions charge for unauthorized financial services by the account holders, that is, that automatically discounts the user from the referred system for services that were not requested and that were never contracted. Thus, cases have been identified that show the problem previously exposed and which occurs in a widespread way in society. To fulfill the proposed objectives, the documentary bibliographic research was used, which allowed access to the rules found in the Organic Monetary and Financial Code, the Constitution of the Republic of Ecuador, and other related regulations that are related to the exposed problem, which were duly analyzed and synthesized by the researcher. From the application of the investigation methods and techniques, it was concluded that the provisions of the Organic Monetary and Financial Code that protect financial users are not observed and that there are no effective mechanisms that allow guaranteeing the rights of bank clients.